Resultados preliminares da estabilidade de cor de laminados cerâmicos cimentados com agente fotoativado e dual: ensaio clínico randomizado - Marchionatti, Ana Maria Estivalete (2014)
The aim of this study was to evaluate color change of ultrathin ceramic laminates cemented with photocuring and dual resin cement by means of a split-mouth randomized clinical trial. The research subjects were 10 post graduation studentsfrom the Program in Dental Sciences, Federal University of Santa Maria. Two 0,3 mm-thick ceramic laminates built with lithium dissilicate ceramic IPS e.max Press (Ivoclar Vivadent) were cemented on the buccal surface of the participants second right and left premolars with the transparent shade of Variolink II (Ivoclar Vivadent), using the dual activation at one side and photoactivation at the other side, by a blind operator regarding the activation mode, after randomizing. The subjects were blind for the groups. Visual color evaluation was performed with a color scale Vita 3D-Master (Vita Zahnfabrik) by a calibrated and blind evaluator; a clinical spectrophotometer Vita Easyshade (Vita Zahnfabrik) was used for instrumental color evaluation 24 hours, 2 months, 4 months and 6 months after cementation. ΔE, Δa*, Δb* and ΔL* between the first and the other evaluations were calculated. Cement marginal staining was also evaluated. Considering visual evaluation, there was no alteration for the parameters value, hue and chroma in the groups. Paired sample t test did not show statistical difference between the groups for the parameters ΔE, Δa*, Δb* e ΔL* during the evaluated intervals. After 6 months, the photocuring group presented a mean ΔE=2,68 (±1,57) and the dual group, ΔE=2,36 (±0,69). Marginal discoloration was not observed. Longer follow-up results are necessary in order to determine if the two curing modes of Variolink II can be used for ceramic veneer cementation.